2020
DOI: 10.3390/pharmaceutics12030232
|View full text |Cite
|
Sign up to set email alerts
|

Metal Organic Frameworks as Drug Targeting Delivery Vehicles in the Treatment of Cancer

Abstract: In recent years, metal organic frameworks (MOFs) have been widely developed as vehicles for the effective delivery of drugs to tumor tissues. Due to the high loading capacity and excellent biocompatibility of MOFs, they provide an unprecedented opportunity for the treatment of cancer. However, drugs which are commonly used to treat cancer often cause side effects in normal tissue accumulation. Therefore, the strategy of drug targeting delivery based on MOFs has excellent research significance. Here, we introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 102 publications
(124 reference statements)
0
78
0
Order By: Relevance
“…42 At present, the most-common active targeting strategy is to connect the targeting ligand to the drug delivery system, which requires the drug system to have an active group to gra the targeting ligand. 43 Laha and colleagues linked folic acid (FA) to the amino group of IRMOF-3 to deliver curcumin to triple negative breast cancer cells. 44 However, it was difficult to modify the FA to the surface of the MOFs without active groups.…”
Section: Discussionmentioning
confidence: 99%
“…42 At present, the most-common active targeting strategy is to connect the targeting ligand to the drug delivery system, which requires the drug system to have an active group to gra the targeting ligand. 43 Laha and colleagues linked folic acid (FA) to the amino group of IRMOF-3 to deliver curcumin to triple negative breast cancer cells. 44 However, it was difficult to modify the FA to the surface of the MOFs without active groups.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 , 6 The ability to control particle size, 7 , 8 , 9 surface chemistry, 10 and internal porosity 11 , 12 has led to increasingly complex MOF-based materials. These have been designed to target specific cells 13 and organelles, 14 transport large specialized cargo such as oligonucleotides and proteins, 15 , 16 , 17 , 18 , 19 release these in response to specific stimuli, 20 , 21 and combine drug delivery with other techniques such as imaging 22 , 23 , 24 , 25 , 26 or photodynamic therapy. 27 , 28 Despite this diversification of material, the process of postsynthetic drug loading itself is often undercharacterized; cargo is often simply assumed to penetrate the porosity of the MOF despite potential competition from loading solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, they suffer from a lack of active targeting and premature metabolism in the body, which reduces their circulation time and poses the risk of early drug release. [69] Interestingly, cancer cell membrane coating technology helps overcome some of the problems with MOF. The first use of the MOF was done by Yue et al, who showed the better killing efficiency of a new drug Berberine by incorporating them in a mesoporous organosilica based MOF.…”
Section: Homotypic Targeting Based Chemotherapymentioning
confidence: 99%
“…Since the last decade, metal‐organic frameworks (MOF) based nanoparticle played an important role, due to their high surface area and easy modification of pore size that leads to better drug loading capacity. Unfortunately, they suffer from a lack of active targeting and premature metabolism in the body, which reduces their circulation time and poses the risk of early drug release [69] . Interestingly, cancer cell membrane coating technology helps overcome some of the problems with MOF.…”
Section: Cancer Therapy Using Cancer Cell Membranementioning
confidence: 99%